Научно-методическое обеспечение дисциплины «Маркшейдерское дело» как средство формирования у студентов профессиональной компетентности - Сысолятина, Т.И.; Бобкова, Е.А.; Щукина, Т.Н. (My University, 2013)
In article scientific and methodical ensuring discipline «Marksheydersky case» as means of formation at students of professional competence is considered. One of main objectives is updating of quality of education. The software of GIS system increases quality of educational process without excessive expenses as allows students to work at a practical example analog of difficult information systems for marksheyder, and also allows to raise a saturation of class periods.